Strategi Pemasaran Dalam Upaya Peningkatan Daya Tarik Pelanggan Pada UMKM Mixue - Muhammad Arrasy Izatullah; Aulia Citra; Arifa Khairiza Azri; Fitri Nuraini Hidayat; Ramdani Bayu Putra (Jurnal Ekonomi dan Bisnis Digital, 2022)
Amid ever-changing market dynamics, MSME Mixue displays an agile response to changing consumer trends and market needs. The use of the latest technology is key in aligning and increasing business efficiency, from inventory management to digital marketing. Technology adoption has also been proven to expand Mixue's MSME market reach and increase interaction with customers. This research documents the creative and proactive adaptation strategies implemented by Mixue MSMEs, illustrating how they not only survive in an era of rapid change but also utilize it as an opportunity for business growth and continuity